2020
DOI: 10.9770/jesi.2020.7.4(9)
|View full text |Cite
|
Sign up to set email alerts
|

Technologies of improving the university efficiency by using artificial intelligence: motivational aspect

Abstract: The aim of this study was to identify the most appropriate technologies to improve the university efficiency by using the motivational artificial intelligence (AI). Methods of the study were as follows: the questionnaire survey by using the Google Chrome electronic service, content analysis, methods of statistical analysis, and a focus group. The authors' version of the questionnaire was made by using the Likert methodology taking into account indicators of the QS World University Rankings rating system. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 33 publications
0
25
0
2
Order By: Relevance
“…All this contributes to the development of their creativity, which remains highly competitive both among humans and in relation to AI [24,25]. The specifics of working with information are significantly modified considering the dynamic development of competencies in working with digital media and the practice of exchanging experience in the network online space.…”
Section: Literature Reviewmentioning
confidence: 99%
“…All this contributes to the development of their creativity, which remains highly competitive both among humans and in relation to AI [24,25]. The specifics of working with information are significantly modified considering the dynamic development of competencies in working with digital media and the practice of exchanging experience in the network online space.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They can be robots in human form. Digitalization is the process of introducing information and communication technologies in all spheres of public life (Vinichenko et al, 2020).…”
Section:  Scientific Objectivesmentioning
confidence: 99%
“…At the same time, another OECD report suggested that the heads of educational organizations and national systems, responding quickly to the situation, had to develop plans for continuing education using alternative teaching methods during the period of the necessary social isolation [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%